Proceedings of the 12th International Conference on Human Computer Interaction With Mobile Devices and Services 2010
DOI: 10.1145/1851600.1851608
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mobile touch interfaces for tetraplegics

Abstract: Mobile touch-screen interfaces and tetraplegic people have a controversial connection. While users with residual capacities in their upper extremities could benefit immensely from a device which does not require strength to operate, the precision needed to effectively select a target bars these people access to countless communication, leisure and productivity opportunities. Insightful projects attempted to bridge this gap via either special hardware or particular interface tweaks. Still, we need further insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…This functional evaluation aimed to produce a more objective capability identification in opposition to lesion level. However, no correlations between participants' characteristics and task performance were found [4]. Regarding technologic experience, all participants had a mobile phone and used it on a daily basis.…”
Section: Participantsmentioning
confidence: 93%
See 1 more Smart Citation
“…This functional evaluation aimed to produce a more objective capability identification in opposition to lesion level. However, no correlations between participants' characteristics and task performance were found [4]. Regarding technologic experience, all participants had a mobile phone and used it on a daily basis.…”
Section: Participantsmentioning
confidence: 93%
“…When asked about the techniques' Ease of Use (using a 5-point Likert scale), the median [quartiles] attributed by the users was for Exiting 2 [2,3], for Tapping 4 [4, 4.5], for Crossing 4 [4,4] and for Directional Gesturing 4 [4,4], showing a slight preference for Tapping. This idea was reinforced when the users were asked about their preferred method (9/15 selected Tapping, 3/15 selected Crossing, and 3/15 selected Directional Gesturing).…”
Section: User Opinionsmentioning
confidence: 99%
“…Touchscreen input also offers the advantage that it requires less strength to use compared to physical buttons [12]. At the same time, many basic touchscreen interactions have proven difficult or in some cases impossible [1,3,9,10,14,16,24,25] For instance, Guerreiro et al [13] measured the accuracy of tapping, crossing, exiting and directional gesturing operations with users with tetraplegia, finding that targets located at the bottom of the screen and next to the preferred hand were the easiest to select. As for multi-touch gestures, Trewin et al [24] found that users with motor impairments encountered difficulties in pinching and performing three-finger slides (confirming [1]).…”
Section: Accessibility Of Touchscreen Inputmentioning
confidence: 99%
“…Request permissions from Permissions@acm.org. with quadriplegia (12mm) [13], and the utility of sliding rather than tapping to reduce input errors for users with tremor [25].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties may be so serious that users refrain from us ing touch devices such as smart phones and tablets. Prior studies in both controlled and real-world settings have con firmed that even the simplest task, single tapping, can require significant effort and time for these users [6,11]. These stud ies have shown that users with motor impairments tend to make more mistakes when selecting their touch targets than users without impairments.…”
Section: Introductionmentioning
confidence: 99%